Discretization of an admixture flux within the framework of a fractal mim model for anomalous diffusion - Maryshev, Boris Sergeevich; Lyubimova, Tatiana Petrovna; Lyubimov, Dmitry Victorovich; Néel, Marie-Christine (Computational Continuum Mechanics, 2010)
The mapping for admixture flux is obtained within the framework of the fractal mobile-immobile model (MIM) describing the non-Fickian effects arising in the admixture filtration process and related to the sticking of particles to the solid matrix. The discretization of the flux for calculations by finite-difference methods is suggested and the conservative scheme for the solution of equations is worked out to take into account the admixture sources. A number of one-dimensional test problems on the admixture transport in the imposed filtrational flow are solved based on the proposed approach.